Green reduction of graphene oxide by using phtoextracts from banana peels - Jiah Chee, Soh (2015)
Graphene is a 2-dimensional (2D) material that attracts many researches interest due to its significant properties and applications. Graphene can be synthesize from oxidation of graphite flakes and reduced by using reductant to become graphene nanosheets. Graphene oxide can be reduced chemically by using reducing agents such as hydrazine or dimethlyhydrazine. However, these chemicals are highly poisonous and toxic, which will bring harmful effect to human beings and environment. Therefore great care is needed when handling these materials and it requires extra routes to remove the impurities introduced by the chemical reduction of graphene oxide such as C-N. To ease the synthesis of good quality and environment friendly graphene, green reduction of graphene oxide becomes an alternative way. In this study, phytoextracts from banana peels was used as the reducing agent due to its high phenolic contents and antioxidant activity. Graphite oxide was fabricated using graphite flakes before undergoing ultrasonication for exfoliation to form the graphene oxide. The graphene oxide was reduced by using phytoextracts from banana peels at room temperature and refluxed temperature. Optimization of phytoextracts reduction was carried out by varying the phytoextracts concentration, reduction time and reduction temperature. The graphene oxide and graphene were characterized by using Ultraviolet-visible spectrophotometer (UV-Vis), Fourier Transform Infrared spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and cyclic voltammetry analysis (CV) for the fabrication of glucose sensor. UV-Vis result for graphene oxide shows an absorption peak at range of 230 nm and red-shifted to 270 nm for phytoextract reduced graphene oxide (PRGO). Graphite oxide (GO) in FTIR study shows intense band at 1623 cm-1 (C=O stretching), 1053 cm-1 (for C-O stretching), and a broad band around 3332 cm-1 for hydroxyl group. PRGO shows the a decrease in the intensity at 3332 cm-1, but does not remove the peak at 1052 cm-1 and 1623 cm-1. PRGO also exhibits a comparable solubility as conventional reduced graphene oxide and in the application of glucose sensor; PRGO was able to detect a glucose concentration of 0.1 mM by using glassy carbon electrode (GCE) at a scan rate of 50 mVs-1.